Geological evidence against large-scale pre-Holocene offsets along the Karakoram Fault: Implications for the limited extrusion of the Tibetan plateau - Searle, M (1996)
Two end-member models proposed to accommodate the convergence between India and Asia north of the Himalaya are (1) homogeneous crustal thickening of the Tibetan plateau and (2) continental escape, or extrusion, of Tibet and southeast Asia, away from the indenting Indian plate. Foremost among the arguments supporting the latter would be large-scale (∼1000-km) offsets and high present-day slip rates along the major strike-slip faults bounding the postulated extruding crust, notably the Altyn Tagh Fault along the northern margin of Tibet and the Karakoram Fault along the SW margin. Satellite photographic interpretation and field mapping in the Karakoram mountains in Pakistan, the Nubra-Siachen area of north Ladakh, and the Pamirs in Xinjiang show that although the Karakoram Fault is extremely active today, geological offsets along the right-lateral fault are probably less than 120 km. The 21±0.5 Ma Baltoro monzogranite-leucogranite batholith has been rotated clockwise about a vertical axis 35°-40° into NW-SE alignment, parallel with the Karakoram Fault, east of the Siachen glacier, with a maximum offset of 90 km across the fault. The Bangong-Shyok suture zone similarly has a dextral offset of 85 km. The course of the Indus River, which was antecedent to the rise of the Ladakh, Karakoram, and Himalayan ranges, has been offset dextrally by 120 km south of Pangong Lake. If present-day slip rates (approximately 32 mm/yr) (Avouac and Tapponnier, 1993) are correct, only 4 Ma are required to obtain a 120-km offset. There is no geological evidence for any larger-scale pre-Holocene offsets, and it is suggested that the Karakoram Fault cannot have accommodated major eastward lateral motion of Tibetan crust. The fault has also exerted little or no influence on surface topographic uplift, cutting obliquely across the highest peaks of the Karakoram. Dextral motion along the central part of the Karakoram Fault has been transferred in the north to the Rangkul, Murghab, and Karasu transpressional faults in the central Pamir. North of Tashkurgan, the Karakoram Fault shows mainly normal motion around the Kongur and Mustagh Ata gneiss domes (metamorphic core complexes) and the extensional Muji graben. Minor dextral displacement has occurred along the Shiquanhe Fault, but this motion cannot be linked to the Jiale Fault of east Tibet. The southern end of the Karakoram Fault merges with the Indus (Yarlung) suture zone near Mount Kailas and does not cut across the Himalaya. The lack of large-scale geological offsets along the Karakoram Fault, together with its very recent initiation (?5 or 4 Ma), suggests that it is related to the Pliocene-Quaternary northward indentation of the Pamir, and not to any long-term extrusion of Tibetan crust following the Indian collision.